Polyvinyl chloride: chemical modification and investigation of structural and thermal properties. (4th July 2021) - Edraki, Milad; Sheydaei, Milad; Alinia-Ahandani, Ebrahim; Nezhadghaffar-Borhani, Erfan
ABSTRACT: In this study, polyvinyl chloride (PVC) was largely dechlorinated using sodium trisulfide (Na2 S3 ) and ethanol. During the process, we successfully incorporated trisulfide bonds into the PVC structure. The structural characteristics of the samples were identified by Fourier transform infrared (FTIR) spectroscopy. The morphological and thermal properties of the samples were studied using X-ray diffraction (XRD) and differential scanning calorimetry (DSC) and thermogravimetric analysis techniques (TGA), respectively. The amounts of chlorine and sulfur were measured by energy-dispersive X-ray spectroscopy (EDX). Also, proton nuclear magnetic resonance ( 1 H NMR) was used to confirm the chemical structure. Moreover, the Na2 S3 was characterized by Ultraviolet–visible-near infrared (UV-VIS-NIR) spectroscopy. The results showed that, with the addition of sulfur to the PVC, the crystallinity is partly reduced. The thermal behaviors of the samples showed that after modification, the glass transition temperature and melting temperature would occur at lower temperatures. In addition, the degradation of the sulfur samples included three DTGA peaks. Furthermore, the presence of sulfur caused a change in the degradation temperature and weight loss during these stages. GRAPHICAL ABSTRACT: UF0001